Predsednik gerentskega sveta, ljubljanski župan in predsednik Mestne občine Ljubljana dr. Dinko Puc (1924-1935) - Perovšek, Jurij (Studia Historica Slovenica, 2017)
Dr. Dinko Puc (1879-1945) led Ljubljana in various postings. Between 1924 and 1926 he was the president of its Elder council, from 1927 to 1929 he was the mayor of Ljubljana, and then in 1935 he was the president of the City municipality of Ljubljana. While he was at the helm of Ljubljana there was a lot of developmental progress in utility services, economy, and urbanism (here he turned to Jože Plečnik). Among the urban additions a special mention should be given of Tromostovje ("Three bridges"), Čevljarski and Trnovski bridges, regulation of Ljubljanica and Gradaščica Rivers, and a thorough restoration of the Ljubljana castle. 900 new building were erected. With great investments Puc had managed to accumulate a lot of debt for the city, which it continued to pay back for a long time to come. However, what was created on his initiative remained and still gives Ljubljana its character. Politically Puc tied Ljubljana firmly with Yugoslav unitarism, however, through his contacts with influential domestic and foreign guests he affirmed the awareness about Ljubljana and Slovenia in the international community. Puc went down in history as an extremely diligent, restorative, modern, and visionary mayor of Ljubljana with an unquestionable understanding for the needs of his city.
Keywords: Ljubljana; lokalna samouprava; Puc, Dinko; Slovenija; zgodovina; župani